A robust [11C]acetate synthesis on a TRACERLab FX C pro module. (October 2022) - Wenz, Jan; Arndt, Felix; Samnick, Samuel
Abstract: Carbon-11 labelled acetate ([ 11 C]acetate) is a radiotracer of importance in clinical practice as well as in preclinical research. The TRACERLab FX C Pro Synthesizer can be used this sensitive carboxylation reaction. Starting from 11 GBq [ 11 C]CO2, we were able to isolate about 3 GBq [ 11 C]acetate after only 20 min reaction time (yield 56 ± 7%, n = 10). Highlights: - Handling of sensitive substances for radiolabeling. - Disposable products for gmp compliant radiopharmaceutical production. - Fully automated synthesis modules flexible for research, preclinic and patient care.